Results of hysteroscopic management of endometrial pathology through laser diode in naval medical center: number of cases - Aldama, Yanet Fermin; Villán, Cesar Rodriguez; Flores, Sara E. Hernández (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysteroscopy consists of an excellent technique for the diagnosis of uterine pathology, the diode laser for treatment has been included, which is energy in the form of a beam of light, monochromatic and coherent, equipped with a great capacity to cut tissues and vaporize them. Objective of this study was to know the result of the hysteroscopic treatment with diode laser, in patients of reproductive age with uterine pathology in the naval medical center of Mexico for a period of one year. Methods: A descriptive study was carried out in 8 patients, with abnormal uterine bleeding and uterine pathology, to know the result of the hysteroscopic treatment with diode laser, inclusion criteria were age of 18 to 40 years, uterine pathology, without previous treatments, exclusion criteria were pregnancy, medical treatment, does not accept the procedure, in a period of September 1, 2017 and September 1, 2018 at the Naval Medical Center of Mexico, the 45-watt 980 nm and 1470 wavelength diode laser console nm with 3fr extra flexible conical tip glass fibers. Results: The average age 29.9±8.5 years, without comorbidities; 60% had an initial diagnosis of endometrial thickening and abnormal uterine bleeding and 40% had a diagnosis of infertility, the most frequent pathology is an endometrial polyp, during the procedure none of the patients required analgesia or post-surgical sedation. The average bleeding was 24.44 ml. Conclusions: The hysteroscopic removal of uterine pathology with diode laser was performed without anesthesia, in an outpatient, feasible and safe way, the surgical time is reduced, with a follow-up of 12 months without recurrence.